2016
DOI: 10.1038/modpathol.2015.126
|View full text |Cite
|
Sign up to set email alerts
|

p16 staining has limited value in predicting the outcome of histological low-grade squamous intraepithelial lesions of the cervix

Abstract: In order to evaluate the usefulness of p16 staining in predicting the outcome of histological low-grade squamous intraepithelial lesion/cervical intraepithelial neoplasia grade 1 (LSIL/CIN1) we prospectively recruited all the patients referred to colposcopy from 2003 to 2011 due to abnormal screening test results and diagnosed with LSIL/CIN1 at biopsy (n = 507). All biopsies were stained for p16 and re-evaluated after three years by the same gynecological pathologist using the LAST criteria. Follow-up was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 36 publications
2
16
2
Order By: Relevance
“…Factor Associated with Recurrent to CIN2 or Worse in HSIL from those studies were inconclusive. The statistical difference was obvious in 2 studies (Liao et al, 2014;Razmpoosh et al, 2014) whereas not statistically different in another 2 studies (Pacchiarotti et al, 2014;Sagasta et al, 2016). In the present study, high-grade lesion with positive p16 staining had recurrence to CIN2+ about 2.13 times than those with negative p16 staining but it was not significantly different.…”
Section: Discussioncontrasting
confidence: 68%
“…Factor Associated with Recurrent to CIN2 or Worse in HSIL from those studies were inconclusive. The statistical difference was obvious in 2 studies (Liao et al, 2014;Razmpoosh et al, 2014) whereas not statistically different in another 2 studies (Pacchiarotti et al, 2014;Sagasta et al, 2016). In the present study, high-grade lesion with positive p16 staining had recurrence to CIN2+ about 2.13 times than those with negative p16 staining but it was not significantly different.…”
Section: Discussioncontrasting
confidence: 68%
“…Liao et al (19) conducted a prospective population-based study to evaluate if the overexpression of p16 INK4a in LSIL biopsies can accurately predict HSIL progression and found that p16 INK4a expression in LSIL on initial diagnosis was associated with an increased risk of HSIL in 2 years (OR=1.43; 95% CI, 0.52-3.91). However, Sagasta et al (20) showed that HSIL/CIN2-3 exhibited higher positive rates for p16 INK4a staining compared with persistent or regressing LSIL/CIN1 lesions (71 vs. 44%), but found that p16 INK4a immunostaining was not associated with risk of HSIL [hazard ratio 1.6 (95% CI, 0.9-2.6); P=0.095]. Sagasta et al (20) subsequently concluded that p16 INK4a overexpression in biopsies from women with LSIL was a poor predictor in LSIL progression, with little or no value as a marker in clinical practice.…”
Section: Discussionmentioning
confidence: 97%
“…It is therefore possible that p16 INK4a , Ki-67 and ProExC can be applied as early HSIL and cervical cancer risk indicators in early cervical lesions. However, to the best of our knowledge, there have been limited studies on the predictive value of p16 INK4a and Ki-67 for LSIL prognosis with inconsistent results (19)(20)(21), whilst the use of ProExC staining as a biomarker for LSIL prognosis has not been previously reported.…”
Section: Introductionmentioning
confidence: 99%
“…Among these latter, p16 ink4 , the HPV viral load and genotyping were the most investigated. Although, all gave some indications on high-risk patients, a lack of concordance has been extensively reported and all failed to precisely predict CIN, which will finally progress to cancer [68,69,70,71,72,73,74,75]. …”
Section: Dualistic Model Of Hpv-related Carcinogenesismentioning
confidence: 99%